2015
DOI: 10.1016/j.jebdp.2015.10.001
|View full text |Cite|
|
Sign up to set email alerts
|

Appropriate Recall Interval for Periodontal Maintenance: A Systematic Review

Abstract: Objectives-A systematic review of the literature was undertaken to assess the evidence to support a specific time interval between periodontal maintenance (PM) visits.Methods-Relevant articles were identified through searches in MEDLINE, EMBASE and PubMed using specific search terms, until April, 2014, resulting in 1095 abstracts and/or titles with possible relevance. Critical Appraisal Skills Programme (CASP) guidelines were used to evaluate the strength of studies and synthesize findings. If mean recall inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 50 publications
0
55
0
Order By: Relevance
“…During SPT, in patients demonstrating stability, the intervals are increased to 4 or 6 months. According to a recent systematic review, however, the evidence of a lifelong interval of 3 months is weak and intervals of 4-12 months could not be recommended from PPD profiles of periodontitis patients enrolled in SPT (Farooqi, Wehler, Gibson, Jurasic, & Jones, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…During SPT, in patients demonstrating stability, the intervals are increased to 4 or 6 months. According to a recent systematic review, however, the evidence of a lifelong interval of 3 months is weak and intervals of 4-12 months could not be recommended from PPD profiles of periodontitis patients enrolled in SPT (Farooqi, Wehler, Gibson, Jurasic, & Jones, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For natural dentition, a 5‐year observation study showed shorter recall intervals could be more favorable in plaque reduction and help reduce bleeding tendency but not be additionally beneficial to other clinical parameters (Rosén et al, ). Furthermore, one systemic review failed to prove the necessity of fixed recall interval regimens within 3–6 months (Farooqi, Wehler, Gibson, Jurasic, & Jones, ). In harmony with the findings, one study obtained the results that frequency of visits could not have impacts on peri‐implant health (Ferreira et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Risk assessment and the subsequent determination of the maintenance interval are controversial topics in the literature [6303132]. Evidence regarding how to determine the maintenance interval in SPT is still weak [6].…”
Section: Discussionmentioning
confidence: 99%
“…During SPT, a risk-adapted maintenance interval must be determined, which allows each individual patient to receive appropriate treatment [6]. The classical parameters that serve as a basis for risk assessment are periodontal probing depth (PPD), bleeding on probing (BOP), bone loss in relation to the patient's age, tooth loss, records of pre-existing systemic diseases (e.g., diabetes), and environmental risk factors, such as smoking habits [7].…”
Section: Introductionmentioning
confidence: 99%